Ordering legal evidences and its underpinning in the usuli research - Mat Jubri@Shamsuddin, Mustafa (Zes Rokman Resources, 2019)
The subject of evidences is one of the most important subjects in the science of principles of jurisprudence because it is based on the legal evidences in terms of theory and practice. If the provisions are descriptions of the acts of the mankind and if the purposes are the objectives of these acts, the means to which they are referred are the legal evidences. The basic standard in dealing with the legal evidences knowing their orders and ranks among themselves, in which the priority of preference should be given to the one that deserves it. This ordering completes the consideration of the evidence and the reasoning in which the error and ignorance leads to deviation in applying legal evidences. This research seeks to study the order of evidences by rooting it in the Quran and Sunnah and the uses of the scholars, and its consequent in theory and practice. This research consists of two sections. The first section deals with the concept of the arrangement of evidence and the legal evidence on it. The second section deals with the arrangement of the legal evidences in usuli research.